อุบัติการณ์การบาดเจ็บของทีมนักกีฬารักบี้ประเภทผู้เล่น 15 คน มหาวิทยาลัยศรีนครินทรวิโรฒ ในกีฬามหาวิทยาลัยแห่งประเทศไทยครั้งที่ 37 (INCIDENCE OF INJURY IN AMATEUR RUGBY FIFTEEN PLAYERS OF SRINAKHARINWIROT UNIVERSITY TEAM IN THE 37TH UNIVERSITY GAME IN THAI) - Krityakiarana, Warin; Phucharoen, Pakaporn (วารสารมหาวิทยาลัยศรีนครินทรวิโรฒ สาขาวิทยาศาสตร์และเทคโนโลยี, 2013)
วัตถุประสงค์ของการศึกษาในครั้งนี้เพื่อศึกษาถึงอุบัติการณ์ ตำแหน่ง และกลไกการบาดเจ็บของทีมนักกีฬารักบี้ประเภท 15 คน ของมหาวิทยาลัยศรีนครินทรวิโรฒ ในกีฬามหาวิทยาลัยแห่งประเทศไทยครั้งที่ 37 ณ มหาวิทยาลัยธรรมศาสตร์ วิทยาเขตรังสิต จังหวัดปทุมธานี โดยจำนวนนักกีฬาในทีมที่เข้าร่วมการฝึกซ้อม และแข่งขันทั้งสิ้น 30 คน เก็บข้อมูลโดยนักกายภาพบำบัด และผู้ฝึกสอนด้วยแบบสอบถามการบาดเจ็บของนักรักบี้จาก Gabbett TJ (2003) ข้อมูลที่ได้จะทำการเก็บข้อมูลจากช่วงระยะเวลาการฝึกซ้อมและการแข่งขัน และคำนวณเปรียบเทียบ 1,000 ชั่วโมงการเล่น ผลการศึกษาพบว่า อุบัติการณ์การบาดเจ็บที่พบในช่วงการแข่งขันเท่ากับ 119.017 ต่อ 1,000 ชั่วโมงการเล่น (Playing hours) (67.45%) และในช่วงฝึกซ้อมเท่ากับ 1.233 ต่อ 1,000 ชั่วโมงการเล่น ตำแหน่งของร่างกายที่ได้รับบาดเจ็บที่พบได้มากที่สุดในการศึกษานี้ ได้แก่ ข้อเท้า และเท้า โดยพบว่า เป็นการบาดเจ็บของกล้ามเนื้อและเอ็นยึดข้อต่อเป็นหลักในทีมผู้เล่นนี้ นอกจากนี้การบาดเจ็บที่พบจะมีมากในช่วงการแข่งขัน การศึกษานี้พบว่า ปัจจัยที่มีผลต่อการบาดเจ็บได้แก่การเกิดการล้า การเกิดการบาดเจ็บซ้ำ ด้านอุณหภูมิ สภาพสนามแข่งขัน หรือสนามฝึกซ้อม ประสบการณ์ของผู้เล่น และจำนวนนักกีฬา ต่างมีผลต่ออุบัติการณ์การบาดเจ็บในการแข่งขัน และการฝึกซ้อม ซึ่งข้อมูลที่ได้นี้สามารถนำไปประยุกต์ใช้ในการให้การดูแลป้องกันการบาดเจ็บของทีมนักกีฬารักบี้ต่อไป คำสำคัญ: กายภาพบำบัด การปะทะ ระบาดวิทยา การฝึกซ้อม It was the purpose of this study to investigate the incidence, site, and mechanism of injuries in fifteen amateur rugby players of Srinakharinwirot University team in the 37th University game at Thammasat University, Rangsit Campus, Pathum Thani, Thailand. A total of 30 players from rugby team, Srinakharinwirot University, joined in this game. The data were collected by physical therapists and the head coach by using checklist from Gabbett TJ (2003). All injured data during practice and competition match were recorded. The incidence in competition of injury was 119.017 per 1,000 playing hours (64.45%) and during training was 1.233 per 1,000 playing hours (35.55%). The most common site of injuries was the area of ankle and foot. The sprain and overuse injury were commonly found in this study. The results show that muscular injuries and injuries of the ankle and foot were the most common injury in fifteen rugby players. Furthermore, injuries were found mostly in competition period. These finding suggest that fatigue microtrauma, temperature, athletic experience, number of players and surface of the field may contribute to the injuries of fifteen rugby players of Srinakharinwirot University team. The professional health care and team can apply this data for prevention of rugby players. Keywords: Physical therapy, Collision, Epidemiology, Training